Cost of ambulatory care by mobile health clinic run by a Medical College in India for the year 2008-09 - Aslesh Prabhakaran; Anand Krishnan; Baridalyne Nongkynrih; Anil Goswami; Chandrakant S Pandav (Wolters Kluwer Medknow Publications, 2014)
Background: The feasibility of using mobile health clinics (MHCs) to deliver health services in urban poor areas has to be explored as the health needs of the residents are not sufficiently addressed by the existing primary health care delivery system in India. Objective: To estimate the cost of providing primary health care services and the out of pocket expenditure (OOPE) incurred, while utilizing these services provided through the MHC based Urban Health Program of a Medical College in North India for the year 2008-2009. Materials and Methods: A cross-sectional study to estimate OOPE was conducted among 330 subjects selected from patients attending the mobile health care facility. For estimation of provider cost, 5 steps process involving identification of cost centres, measurement of inputs, valuing of inputs, assigning of inputs to cost centers, and estimation of unit cost were carried out. Results: Total annual cost of providing services under Urban Health Program in the year 2008-2009 was Rs. 7,691,943 Unit cost of providing outpatient curative care, antenatal care, and immunization were Rs. 107.74/visit, Rs. 388/visit and Rs. 66.14 per immunization, respectively. The mean OOPE incurred was Rs. 29.50/visit, while utilizing outpatient curative services and Rs. 88.70/visit for antenatal services. Conclusion: The MHC can be considered as a viable option to provide services to urban poor.